Wake - Hocking, Amanda (Watersong, 2012)
In the quiet seaside town of Capri, sixteen-year-old Gemma enjoys a close bond with her sister Harper and a growing attraction to next-door neighbor with Alex, but everything changes when, after partying with newcomers Penn, Lexi, and Thea, Gemma discovers she has powers that will force a terrible choice.